2023
DOI: 10.1001/jamainternmed.2023.2215
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Technology Assisted Stepped Collaborative Care Intervention to Improve Symptoms in Patients Undergoing Hemodialysis

Abstract: ImportancePatients with end-stage kidney disease (ESKD) undergoing long-term hemodialysis often experience a high burden of debilitating symptoms for which effective treatment options are limited.ObjectiveTo compare the effectiveness of a stepped collaborative care intervention vs attention control for reducing fatigue, pain, and depression among patients with ESKD undergoing long-term hemodialysis.Design, Setting, and ParticipantsTechnology Assisted Stepped Collaborative Care (TĀCcare) was a parallel-group, s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 61 publications
0
6
0
Order By: Relevance
“…The studies in our review were subject to certain limitations. This included insufficient results to draw any conclusions [ 12 ], challenges in generalizing the findings [ 13 , 15 , 27 , 35 , 48 , 50 , 51 ], language difficulties among patients [ 13 ], a lack of detail on the effect of the intervention elements [ 13 ], the possibility of contamination of information between patient groups [ 14 , 19 , 34 , 44 ], uncontrolled variables [ 14 , 21 , 22 , 26 , 29 , 31 , 37 ], short duration of studies, interventions, or follow-up [ 15 , 19 , 27 , 30 , 35 , 41 , 51 ], the patients already being familiar with educational content [ 17 ], small sample size [ 29 , 30 , 37 , 41 , 46 , 49 , 52 ], self-selection bias [ 52 ], not all information being analyzed [ 20 , 48 ], subjective results linked to patient declarations [ 23 ], inaccurate assessment tools [ 42 ], possible Hawthorne effect [ 30 ], interventions conducted in a single center [ 30 , 41 ], and the possibility of social desirability effect bias [ 39 ,…”
Section: Discussionmentioning
confidence: 99%
“…The studies in our review were subject to certain limitations. This included insufficient results to draw any conclusions [ 12 ], challenges in generalizing the findings [ 13 , 15 , 27 , 35 , 48 , 50 , 51 ], language difficulties among patients [ 13 ], a lack of detail on the effect of the intervention elements [ 13 ], the possibility of contamination of information between patient groups [ 14 , 19 , 34 , 44 ], uncontrolled variables [ 14 , 21 , 22 , 26 , 29 , 31 , 37 ], short duration of studies, interventions, or follow-up [ 15 , 19 , 27 , 30 , 35 , 41 , 51 ], the patients already being familiar with educational content [ 17 ], small sample size [ 29 , 30 , 37 , 41 , 46 , 49 , 52 ], self-selection bias [ 52 ], not all information being analyzed [ 20 , 48 ], subjective results linked to patient declarations [ 23 ], inaccurate assessment tools [ 42 ], possible Hawthorne effect [ 30 ], interventions conducted in a single center [ 30 , 41 ], and the possibility of social desirability effect bias [ 39 ,…”
Section: Discussionmentioning
confidence: 99%
“…Details of the study design have been reported elsewhere. 17 This study was approved by the University of Pittsburgh's Institutional Review Board and the University of New Mexico's Human Research Review Committee. Participants were treated in accordance with the Declaration of Helsinki.…”
Section: Methodsmentioning
confidence: 99%
“…Details of the study design and primary outcome results have been reported elsewhere. 19 Adult (18 years or older), English-speaking patients undergoing thrice-weekly maintenance HD for .3 months from 14 free-standing dialysis clinics (Dialysis Clinic, Inc.) participated in symptom screening. Those with evidence of thought disorder, delusions, or active suicidal intent; active substance abuse; too ill or cognitively impaired to participate based on clinicians' judgment; anticipated life expectancy of ,1 year; scheduled for living donor kidney transplant; or relocating to another dialysis unit within 6 months were excluded.…”
Section: Study Populationmentioning
confidence: 99%
“…The Technology Assisted stepped Collaborative Care (TĀCcare) study was a multicenter randomized controlled trial (RCT) designed to compare the effectiveness of a stepped collaborative care intervention for symptom management in HD patients. 18 , 19 Given the high prevalence and cooccurrence, negative health effect, and lack of treatment options, the symptom cluster of fatigue, pain, and depression was targeted in the RCT. The main objective of this report was to identify differences in rates of symptom burden and readiness to engage in treatment by sociodemographic factors in HD patients.…”
Section: Introductionmentioning
confidence: 99%